Phenotypic charactheristics of fluorescent pseudomonss, biological control agent of lincat disease of temanggung tobacco - TRIWIDODO ARWIYANTO; YMS MARYUDANI; NINING NURUL AZIZAH (Biodiversitas Journal of Biological Diversity, 2007)
Fluorescent pseudomonass isolated from local plants rishosphere in temanggung controlled lincat disease of tobacco. This report describe phenotypic charactheristics of the bacteria in order to be used as a base for the development of the bacteria as a biological control agent of lincat disease. Phenotypic charactheristics of six isolates of fluorescent Pseudomonass which controlled lincat disease in the field weredetermined in the laboratory of Plant Bacteriology, Faculty of Agriculture, Gadjah Mada University. Plant pathogenicity tests were conducted by hypersensitive reaction into tobacco leaf and inoculation to tobacco plants. Antagonism test between fluorescent Pseudomonass and other candidate of biological control agents were also conducted. The results indicated that the bacteria were rod shape, Gram negative, positive reaction in catalase and oxidase tests. Nitrate reduce to nitrite, arginine was hydrolysed, fluorescent pigment were produced on Kingâ€™s B medium, levan formation positive and all bacteria denitrifiy. The bacteria used urea, tween 80 and amylum were not hydrolised, poly- -hydroxybutyrate was not accumulated in the cells. Negative reactions were observed for lysine decarboxylation, indol production, VP/MR reaction, and gelatn liquefation. Some compounds could be used as solely carbon sources. All isolates grew on the medium containing 2% NaCl. The best pH for growth was 6-7 and all isolates grew at 20-41C. Negative result were obtained for hypersensitive reaction and pathogenicity tests.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: fluorescent Pseudomonas, phenotypic characteristics, tobacco, lincat disease